The Minimum Age Of Criminal Responsibility In Brunei Darussalam: A Comparative Analysis Of The Penal Laws - Ahmad Masum; Yusuf Ibrahim Arowosaiye; Hj Hanan Hj Abd Aziz; Rajali Aji (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
This article examines the Minimum Age of Criminal Responsibility (MACR) in Brunei Darussalam, and the intricacies of its two legal systems including the civil law and the Syariah law. Central to juvenile justice, the issue of criminal responsibility concerns moral culpability and developmental capacity, especially amidst Brunei Darussalam's low seven-year MACR, which contrasts with international advocacy for higher thresholds. The article examines the conceptual principles of MACR and evaluates its implementation in accordance with the international child rights norms, such as the United Nations Convention on the Rights of the Child (UNCRC), the Beijing Rules, and the Riyadh Guidelines. Through a qualitative doctrinal approach, it analyses the current legislation and practice and finds that despite the legal context being welfare-focused, the low MACR negatively influences the possibility of a rehabilitative juvenile justice system. To meet the international standards, the article recommends that the MACR should be raised, and the age limits in both legal systems be equalised to align with each other. This article enriches the global discussion by providing a focused analysis of juvenile criminal responsibility in a Syari'ah context and participating in the comparison with other jurisdictions maintaining low MACR levels.